Attitudes of men towards birth control measures practiced by women in Mamitwa Area Tzaneen Limpopo Province - Radzuma, Ndifelani Daphney (My University, 2021)
Background: This study sought to understand men's attitudes towards birth control measures practised by their partners in the Mamitwa area located in the Greater Tzaneen Municipality, which falls under the Mopani District in Limpopo Province of South Africa. Methods: A qualitative descriptive study using Focus Group Discussions (FGDs) with purposively selected men aged 25-60 years in a relationship with women of childbearing age was conducted in 2019 in the Mamitwa area. Open-ended question guide was used to explore men perceptions regarding Family Planning and discussions were recorded, translated, and transcribed verbatim. Transcripts were coded and analysed thematically. Results: Three major themes were identified, namely: (i) Perceived advantages of Family Planning, including financial benefits, Prevention of STIs and unwanted pregnancy; (ii) Perceived disadvantages of Family Planning, including adverse effects of Family Planning on men and women and marital difficulties; and (iii) Communication with men about Family Planning, including healthcare workers, were being blamed for excluding men in Family Planning discussions. Conclusion: Men had favourable attitudes towards Family Planning use. However, there is a lack of adequate information about Family Planning, thus causing men to doubt allowing their respective female partners to use Family Planning. This underscores the need to educate and involve men in Family Planning programs. Key Concepts: Family Planning; Attitudes; Perception; Men Family Planning Use
Thesis (M. A. (Family Medicine) -- University of Limpopo, 2021
Keywords: Family planning; Attitudes; Perception; Men family planning use; Birth control -- South Africa; Birth control -- Moral and ethical aspects; Family planning -- South Africa -- Limpopo